S27 A placebo-controlled, double-blind, randomised, crossover study to assess the efficacy, safety and tolerability of TRPV4 inhibitor GSK2798745 in participants with chronic cough. (12th November 2019) - Ludbrook, VJ; Hanrott, KE; Marks-Konczalik, J; Kreindler, JL; Bird, NP; Hewens, D; Beerahee, M; Behm, DJ; Morice, A; McGarvey, L; Parker, SM; Birring, SS; et al.
Abstract : Introduction and objectives: Airway sensory nerves involved in the cough reflex may be mediated by adenosine triphosphate (ATP) agonism of P2X purinoceptor 3 (P2X3) receptors. Transient receptor potential vanilloid 4 (TRPV4) activation causes ATP release from airway macrophages and epithelial cells and it is hypothesised that a TRPV4-ATP-P2X3 axis contributes to chronic cough. The aim of this study was to evaluate, using an adaptive design, whether blockade of TRPV4 channels, using the selective TRPV4 channel blocker GSK2798745, is effective in reducing cough. Methods: A placebo-controlled, double blind, randomised, two-period crossover study was designed with interim analyses for futility and to allow possible sample size adjustment during the study. Refractory chronic cough patients were recruited from four specialist clinics. Participants received either GSK2798745 or matching placebo once daily for 7 days with a 14–21 day wash out between treatments. Dose of GSK2798745 orally administered was predicted to give ∼65–72% TRPV4 inhibition over 24-hour period. Blood samples were collected for pharmacokinetic assessment. 24-hour cough count (VitaloJAK) was recorded before and after each treatment period. The primary endpoint was total cough counts during day-time hours following 7 days of dosing. Results: Interim analysis was performed after 12 participants had completed both treatment periods and showed a 32% increase in cough counts on Day 7 for GSK2798745 compared to placebo. The negative criteria for the study were met and the study was subsequently stopped. At this point 17 participants had been enrolled (Mean 61yrs; 88% female), and 15 completed the study. Final study results for posterior median cough counts are shown in table 1. Conclusion: There was no evidence of an anti-tussive effect of GSK2798745, despite cough frequency being highly reproducible within patients and expected drug exposure. Leicester Cough Questionnaire and severity and urge to cough VAS were consistent with this lack of change in cough counts. The design of the study allowed the decision on lack of efficacy to be made with minimal participant exposure to the molecule.